PENGARUH NETWORKING DAN TRUST TERHADAP PENINGKATAN PENJUALAN KARET REMAH PADA PT. NUSIRA MEDAN - harun harun; Nur'ain Harahap (JURNAL MANAJEMEN DAN BISNIS, 2022)
This study aims to determine whether there is an effect between Networking and Trust on increasing crumb rubber sales. In this study the authors used descriptive and quantitative analysis with a sample of 50 employees at PT. Nusira Medan. This study was used by distributing questionnaires to employees of PT. Nusira Medan. The results showed that Networking and Trust had an effect on increasing crumb rubber sales at PT. Nusira Medan as shown from the results of multiple regression Y = 3,486+ 0,457X1 + 0, 355X2 + e. On the results of the partial test (t test) of Networking on the increase in crumb rubber sales, the value of tcount = 2.688>1.67 and the partial test value (t-test) of Trust obtained the value of tcount = 2.396>1.67, this shows that partially Networking and Trust has a positive and significant effect on increasing crumb rubber sales at PT. Nusira Medan, in addition to the F test results obtained Fcount>Ftable (28,761>3.195) with a probability level (0.01<0.05). The value of the coefficient of determination (R2) of 0.550 means that Networking and Trust is able to increase the sales of crumb rubber at PT. Nusira Medan. by 55% and the remaining 45% is explained by other variables outside the study.